Gorlin-goltz syndrome, an incidental finding: A rare case report - Sanyasi Gandhiraj (Wolters Kluwer Medknow Publications, 2012)
Gorlin-Goltz syndrome is an uncommonly found rare disease which shows various possible diverse manifestations of multisystem anomalies, high degree penetration rate with variable expressiveness at least on three body systems. Cutaneous, skeletal, ophthalmological, neurological and reproductive systems are commonly affected in this syndrome. Multiple keratocysts of the jaws are the frequently developed early abnormality than any other. Hereditary autosomal dominant trait is explained as the causative factor for the development of the syndrome. In this case two major and seven minor anomalies were registered. The anomalies found in the patient were not categorized as serious life-threatening abnormalities excepting the multiple keratocysts which were treated by enucleation, curettage and Camoy's solution application. An incidental detection of Gorlin-Goltz syndrome with multisystem anomalies of a 14-year-old female patient, who had reported for the swelling in the left body of the mandible, is described in this article.